The Faithfulness of Jesus the Messiah: a Gospel Emphasis - Zorn, Walter D. (Wipf and Stock, 2020)
This book will challenge the reader's understanding of Paul's expression pistis Christou, "faith/faithfulness of Christ," and the use of the pistis word group throughout the New Testament. --Book cover